2022
DOI: 10.1017/s0007114522000927
|View full text |Cite
|
Sign up to set email alerts
|

Shooting shadows: India’s struggle to reduce the burden of anaemia

Abstract: Despite several efforts by the Government of India, the national burden of anaemia remains high and its growing prevalence (between 2015-2016 and 2019-2021) is concerning to India’s public health system. This article reviews existing food-based and clinical strategies to mitigate the anaemia burden and why they are premature and insufficient. In a context where multiple anaemia control programmes are in play, this article proposes a threefold strategy for consideration. First, except the Comprehensive National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…First, although India is celebrating the increased uptake of ≥ 100 IFA (from 30.3% during 2015–16 to 44.1% during 2019–21) 18 , it still needs an appropriate method of anaemia measurement. More research is needed on required dose of iron and long-term effect of iron overdose among pregnant mothers 46 . Second, the Government of India should more stringently monitor and reprehend unnecessary caesarean section delivery, as its high and growing prevalence is concerning 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, although India is celebrating the increased uptake of ≥ 100 IFA (from 30.3% during 2015–16 to 44.1% during 2019–21) 18 , it still needs an appropriate method of anaemia measurement. More research is needed on required dose of iron and long-term effect of iron overdose among pregnant mothers 46 . Second, the Government of India should more stringently monitor and reprehend unnecessary caesarean section delivery, as its high and growing prevalence is concerning 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, finding of this study is consistent with the recommendation of IFA consumption to increase maternal and infant survival. Earlier studies conducted in India [42][43][44][45][46] have discussed the coverage of IFA and possible pathways to improve maternal and child survival in India. A recent study 37 in India analysed nationally representative data and showed that consumption of IFA by pregnant mothers could prevent neonatal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…1 These rates are an increase from the 2015/16 estimates and has raised concerns regarding the effectiveness of anaemia prevention programmes. 2,3 In India, the prevalence of anaemia is highest in the early years, decreases until about 11 years of age and then increases again during adolescence, particularly in girls because of the start of menstruation and as a consequence of early marriage and teenage pregnancy. [4][5][6][7][8] Nutritional anaemia due to lack of iron, folate or vitamin B12 is the most prevalent cause of anaemia in this age group 6 and has long-term negative implications on growth and development, school performance and work productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several decades of programming, anaemia continues to be a critical public health problem in India, affecting 59% of adolescent girls and 31% of boys aged 15–19 years of age 1 . These rates are an increase from the 2015/16 estimates and has raised concerns regarding the effectiveness of anaemia prevention programmes 2,3 . In India, the prevalence of anaemia is highest in the early years, decreases until about 11 years of age and then increases again during adolescence, particularly in girls because of the start of menstruation and as a consequence of early marriage and teenage pregnancy 4–8 .…”
Section: Introductionmentioning
confidence: 99%
“…1 This is an increase from the 2015-16 estimates and has raised concerns regarding the effectiveness of anaemia prevention programs. 2,3 In India, the prevalence of anaemia is highest in the early years, decreases until about 11 years of age and then increases again during adolescence, particularly in girls due to the start of menstruation and as a consequence of early marriage and teenage pregnancy. [4][5][6][7][8] Nutritional anaemia due to lack of iron, folate, or vitamin B12 is the most prevalent form in this age group 6 and has long term negative implications on growth and development, school performance and work productivity.…”
Section: Introductionmentioning
confidence: 99%